The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1111/j.1744-6570.2011.01240.x
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Affect and Leadership During Organizational Change

Abstract: Based on multilevel data collected at 2 points in time, we examine the role of employees’ affective experiences in shaping their commitment and behavioral responses to both the initial (Time 1) and later (Time 2) phases of organizational change (12 months later). We also test the cross‐level effect of workgroup managers’ transformational leadership on their employees’ responses to change. We find strong support for predicted longitudinal relationships between employees’ affective experiences and their commitme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
92
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 113 publications
(107 citation statements)
references
References 112 publications
(177 reference statements)
8
92
0
1
Order By: Relevance
“…Measures assessing employees' level of affective organizational commitment, for example, include items with affective content such as: "I would be very happy to spend the rest of my career with this organization" (emphasis ours, Allen & Meyer, 1990). Consistent with this, higher levels of affective commitment to organizational change have been reported by employees who feel more positive affect during organizational change (Seo et al, 2012); while this finding is with regard to changespecific affective commitment, we posit that this is likely to occur more broadly to one's organization.…”
Section: Pleasant Feelings Foster Positive Job Attitudesmentioning
confidence: 78%
See 1 more Smart Citation
“…Measures assessing employees' level of affective organizational commitment, for example, include items with affective content such as: "I would be very happy to spend the rest of my career with this organization" (emphasis ours, Allen & Meyer, 1990). Consistent with this, higher levels of affective commitment to organizational change have been reported by employees who feel more positive affect during organizational change (Seo et al, 2012); while this finding is with regard to changespecific affective commitment, we posit that this is likely to occur more broadly to one's organization.…”
Section: Pleasant Feelings Foster Positive Job Attitudesmentioning
confidence: 78%
“…This theoretical perspective has been supported by many empirical studies (e.g. Fisher, 2000, Heller & Watson, 2005, Ilies & Judge, 2002, Judge & Ilies, 2004, Seo et al, 2012, Weiss et al, 1999. For example, Weiss et al (1999) showed that employees' pleasant and unpleasant feelings experienced across 16 working days significantly influenced their job satisfaction, independent of their beliefs about their jobs.…”
Section: Pleasant Feelings Foster Positive Job Attitudesmentioning
confidence: 90%
“…These studies have examined the effect of human factors on deal performance from the perspective of company cultures, parallels between company management styles, organizational cultures of tolerance, and other such individual, group, and organizational elements (Seo et al, 2012). We contribute to the existing research in three important ways:…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…Research related to transitional economies is still very limited, although the challenges of managing post-acquisition integration are more serious than those in developed economies, taking into account the unstable institutional context (Meyer, 2002). Further, only few studies researched the importance of transformational leadership on lower hierarchical levels (Seo et al, 2012;Carter et al, 2012). The present study strives to address this research gap by elaborating on the links between transformational leadership (especially at lower hierarchical levels) and post-acquisition performance while introducing the mediating effect of employee attitudes toward changes, in the specific context of a transitional economy.…”
Section: Introductionmentioning
confidence: 99%